Electrical analysis of PVA/PAMPS polymer blend electrolytic membranes. (2021) - Joshi, Alankrita; Prasad, Brijesh; Panwar, Varij
Abstract: The polymer electrolyte membranes have acquired immense interest for scientific community due its various industrial applications in biosensors, fuel cell, piezoresistive sensors, Li ion battery, humidity sensors. Here, we developed the electrolytic membrane and analysed the dielectric behaviour of the Poly-vinyl alcohol (PVA)/poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) in frequency range 20 Hz to 10 MHz for capacitor and Thin Film Transistor (TFT) applications. The membrane showing high dielectric constant has been synthesized by blending PVA and PAMPS together. Initially the dielectric constant of pure PVA membrane was low, but it increased with the addition of PAMPS. The impedance analyzer was used to measure dielectric constant, AC conductivity and dissipation factor. The pure PVA membrane on addition of PAMPs becomes biocompatible because of its low toxicity. In this research paper we have concluded that on adding 0.6 gm of PAMPs to PVA we have got the best result in terms of dielectric constant and conductivity.